Sustainability indicators in municipal waste management in the municipality of Salvaterra (Ilha do Marajó-Pará) (Research, Society and Development, 2022)
The municipality of Salvaterra is located on Ilha do Marajó and is one of the Brazilian municipalities where the final disposal of solid waste still occurs incorrectly. In this sense, the present work aimed to analyze the current scenario of solid waste management in the municipality of Salvaterra/PA through the PEIR (Pressure-State-Impact-Response) sustainability indicator system. The results demonstrate that the waste generated in the municipality is discarded in a dump located near the city and that the health service residues, produced in hospitals, are burned in the open in this same dump. There is no type of solid waste management, soil sealing or treatment of gases generated by the decomposition of city waste, which further aggravates the situation as water resources and soil can be contaminated by leachate, the population is vulnerable to contagion of vector-borne diseases and the burning of healthcare waste contributes to air pollution and can also cause respiratory disease. Thus, it is noted that the system of sustainability indicators PEIR proved to be an effective tool to carry out the first data collection and the municipal diagnosis on the reality of waste in Salvaterra, being, in this way, a starting point that can subsidize actions, stimulate and direct new studies and complement the construction of the municipal waste management plan.